Application of the Audio Lingual Method to Improve Speaking Skills in Indonesian Language Learning for Class II Students of MIS Nurul Ilmi, Bima City - Nadira; Sukrin; Fuaddudin (Literasi: Jurnal Pendidikan Guru Indonesia, 2026)
This study aims to determine the application of the audio-lingual method in improving speaking skills in Indonesian language learning for second-grade students at MIS Nurul Ilmi, Bima City. This type of research is Classroom Action Research. The results of the study concluded that the process of speaking through method ALM (Audio Lingual Method) with the use of Indonesian language videos in cycle II is known to have experienced positive changes compared to cycle I. These changes can be seen from the observation notes that the researcher wrote after carrying out the speaking process using the ALM (Audio Lingual Method) with the use of Indonesian language videos. There was an increase in speaking skills of second-grade students of MIS Nurul Ilmi Kota Bima after conducting research on speaking using the ALM (Audio Lingual Method) method with the use of Indonesian language videos. This increase in speaking skills can be seen from the results of the pre-cycle, cycle I, and cycle II. The average speaking test score in the pre-cycle stage was 60.5 which was in the sufficient category and the completion was 4.167%. In cycle I, the average score reached 67.3 with the sufficient category and the completion was 20.833%. In cycle II, the average score increased by 10.67 from cycle I to 78 with the good category and the completion was 95.833%. There was a change student behavior Class II of MIS Nurul Ilmi, Bima City, after participating in the Indonesian language speaking skills through the ALM (Audio Lingual Method) method and Indonesian language videos, experienced changes in honest, responsible, creative, communicative, independent, tolerant, and democratic behavior in a positive direction.